Pengembangan Skala Karakter Empati Siswa Kelas XI SMA - Santi, Ardhya Wira; Andrianie, Santy; Ariyanto, Restu Dwi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Humans are creatures that cannot be separated from one another, empathy is something that is indispensable for every human being, empathy is said to be the core of emotion, considering the importance of the character of empathy for every human being, this needs to be grown and developed in students. This study aimed to determine the validity and reliability of the empathy scale. Researchers used an instrument development design consisting of: (1) research and informing; (2) planning; (3) developing a preliminary form of product; (4) preliminary field testing; (5) main product revision. The population in this study was 270 students of class XI SMAN 1 Pare with a sample of 30 students. Data analysis was carried out using product-moment correlation and Cronbach's Alpha. From the initial instrument design of 30 items, there were 30 invalid items, leaving 23 valid items while the Cronbach alpha value was 0.852 which was included in the good category. Thus, the instrument is ready to use.